Annam - Tourane - Chambre de Commerce et d'Agriculture - Pierre Dieulefils (Wikimedia Commons, 1930)
Carte postale ancienne issue de Wikimedia Commons. Titre: Annam - Tourane - Chambre de Commerce et d'Agriculture. A postcard depicting the municipal Chamber of Commerce and Agriculture of the Annamese City of Tourane, French Indo-China.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Carte postale